1992
DOI: 10.1111/j.1365-2222.1992.tb00166.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a video questionnaire* with the IUATLD written questionnaire for measuring asthma prevalence

Abstract: A video questionnaire (VQ) for measuring asthma prevalence in adolescents was assessed for repeatability and validity in relation to bronchial hyperresponsiveness (BHR) (PD20 less than or equal to 7.8 mumol methacholine). Comparison was also made with a standard, self completed written questionnaire (SQ), based on the IUATLD Bronchial Symptoms Questionnaire, which included five questions seeking comparable data to those in the VQ. Both the VQ and SQ were administered to 707 schoolchildren (13-16 years), in who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(81 citation statements)
references
References 22 publications
2
74
0
5
Order By: Relevance
“…Both written and video symptom questions from the ISAAC survey were used [12][13][14][15][16]. The 12-14 yr age group was chosen to reflect the period when morbidity from asthma is common and to enable the use of self-completed questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…Both written and video symptom questions from the ISAAC survey were used [12][13][14][15][16]. The 12-14 yr age group was chosen to reflect the period when morbidity from asthma is common and to enable the use of self-completed questionnaires.…”
Section: Methodsmentioning
confidence: 99%
“…• The Childhood Asthma Questionnaire was developed based on literature review, a Delphi approach, and a synthesis of question items previously tested and shown to be predictive [36][37][38][39].…”
Section: Case-finding Toolsmentioning
confidence: 99%
“…Son zamanlarda video anket yönteminin de kullanımı artmaktadır. Video anket yöntemi ile yapılan çalışmalarda yazılı anket yöntemiyle yapılan çalışmalara göre ailelerin vizingi daha iyi tanımladıkları, terminolojiden kaynaklı kısıtlamaların daha az olduğu ve video anket yöntemi ile yapılan çalışmalarda vizing prevalansının daha düşük olduğu saptanmıştır (8)(9)(10).…”
Section: Introductionunclassified